2015
DOI: 10.4103/0972-0707.159726
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of third generation versus fourth generation electronic apex locators in detecting apical constriction: An in vivo study

Abstract: Aim:The aim of this in vivo study was to compare the accuracy of Root ZX and Raypex 5 in detecting minor diameter in human permanent single-rooted teeth.Materials and Methods:Thirty-one patients with completely formed single-rooted permanent teeth indicated for extraction were selected for the study. Crown was flattened for stable reference point and access cavity prepared. Working length was determined with both apex locators. A 15 K file adjusted to that reading was placed in the root canal and stabilized wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
0
6
0
5
Order By: Relevance
“…There are conflicting arguments regarding the accuracies of EALs. Swapna et al ( 33 ), Singh et al ( 34 ) and Altunbas et al ( 35 ) have reported that Raypex 5 was accurate in 93.2%, 91% and 91.7% of the cases, respectively. Somma et al ( 36 ), who had compared the accuracies of Raypex 5, Propex II and Dentaport ZX in an in vivo study, have found that the percentage of EWL accuracy within ± 0.5 mm range was 20% for Raypex 5.…”
Section: Discussionmentioning
confidence: 98%
“…There are conflicting arguments regarding the accuracies of EALs. Swapna et al ( 33 ), Singh et al ( 34 ) and Altunbas et al ( 35 ) have reported that Raypex 5 was accurate in 93.2%, 91% and 91.7% of the cases, respectively. Somma et al ( 36 ), who had compared the accuracies of Raypex 5, Propex II and Dentaport ZX in an in vivo study, have found that the percentage of EWL accuracy within ± 0.5 mm range was 20% for Raypex 5.…”
Section: Discussionmentioning
confidence: 98%
“…Its reliability has been confirmed by a large number of studies and the findings of this study were similar to those of other studies. 25,[31][32][33] The multiple frequency processing technologies and use of RMS (root mean square) incorporated into the Raypex 6 may have theoretical advantages for increasing the accuracy of the working length measurements, by reducing the electrical noises affecting other physical parameters like amplitude or phase of the electrical signal that is used by other EALs. But the technology improvements were not enough to make the Raypex 6 significantly more accurate than the Raypex 5 (p > 0.05), which appears to be an extremely accurate fourth-generation EAL.…”
Section: Discussionmentioning
confidence: 99%
“…Swapna ve ark. 29 33 çalışmalarındaki metodoloji farklılığı nedeniyle mevcut çalışmanın sonuçları paralellik göstermemektedir. Aggarwal ve ark.…”
Section: Discussionunclassified